Combustion characteristic of air staging in gas burner system - Mohd. Jaafar, Mohammad Nazri; Abdul Wahid, Mazlan; Mustafa, Azeman; Ishak, Mohamad Shaiful Ashrul (Universiti Teknologi Malaysia, 2005)
The combustion process from a burner which utilizes gas fuel tends to produce emission containing various hazardous substances such as NOX, CO, CO2 etc. These emissions must be reduced due to it fatal effects that could bring harm to the livings. Thus, a performance study of air staging for this type of burner is essential to ensure that the burner does operate efficiently as well as producing less emission. This technique has also shown improvement in the reduction of NOX emissions of about 13%.